Sensitivity of Meloidogyne incognita and Rotylenchulus reniformis to Abamectin - Faske, T R (Journal of nematology, 2006)
Avermectins are macrocyclic lactones produced by Streptomyces avermitilis. Abamectin is a blend of B(1a) and B(1b) avermectins that is being used as a seed treatment to control plant-parasitic nematodes on cotton and some vegetable crops. No LD(50) values, data on nematode recovery following brief exposure, or effects of sublethal concentrations on infectivity of the plant-parasitic nematodes Meloidogyne incognita or Rotylenchulus reniformis are available. Using an assay of nematode mobility, LD(50) values of 1.56 mug/ml and 32.9 mug/ml were calculated based on 2 hr exposure for M. incognita and R. reniformis, respectively. There was no recovery of either nematode after exposure for 1 hr. Mortality of M. incognita continued to increase following a 1 hr exposure, whereas R. reniformis mortality remained unchanged at 24 hr after the nematodes were removed from the abamectin solution. Sublethal concentrations of 1.56 to 0.39 mug/ml for M. incognita and 32.9 to 8.2 mug/ml for R. reniformis reduced infectivity of each nematode on tomato roots. The toxicity of abamectin to these nematodes was comparable to that of aldicarb